2019
DOI: 10.1038/s41598-019-52574-y
|View full text |Cite|
|
Sign up to set email alerts
|

Treatment response and predictors in patients with newly diagnosed epilepsy in Ethiopia: a retrospective cohort study

Abstract: Epilepsy is a chronic neurological disease with a variable therapeutic response. To design effective treatment strategies for epilepsy, it is important to understand treatment responses and predictive factors. However, limited data are available in Africa, including Ethiopia. The aim of this study was therefore to assess treatment response and identify prognostic predictors among patients with epilepsy at Jimma university medical center, Ethiopia. We conducted a retrospective cohort study of 404 newly diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 39 publications
2
22
1
Order By: Relevance
“… 17 , 40 Two-thirds of patients with controlled seizure achieved seizure control with single ASM use, which was congruent with reports from other sub-Saharan African countries. 16 18 , 21 23 Several Western studies have shown that the response to the first ASM is the best predictor of long-term outcome. Seizures that continued despite adequate doses of an appropriate had a lower chance of subsequent seizure remission.…”
Section: Discussionmentioning
confidence: 99%
“… 17 , 40 Two-thirds of patients with controlled seizure achieved seizure control with single ASM use, which was congruent with reports from other sub-Saharan African countries. 16 18 , 21 23 Several Western studies have shown that the response to the first ASM is the best predictor of long-term outcome. Seizures that continued despite adequate doses of an appropriate had a lower chance of subsequent seizure remission.…”
Section: Discussionmentioning
confidence: 99%
“…Twentythree primary studies were included in the present systematic review and meta-analysis. These studies were conducted in different parts of Ethiopia (from Amhara seven primary articles [7,[13][14][15][16][17][18], Oromiya eight [8,9,[19][20][21][22][23][24], Addis Ababa four [25][26][27][28], Tigray two [9,29], and Southern Nation, Nationalities, and People two articles) [30,31]. The sample size of the included primary studies was considerably variable ranging from 121 to 415 participants.…”
Section: 2mentioning
confidence: 99%
“…Regarding the seizurefree period, two studies assessed seizure freedom over one month [6,21], one study over two months [17], two studies over three months [7,14,25], and the remaining studies assessed seizure freedom over at least six months. Concerning the age groups, one study included only pediatric patients [7], two studies included all age group patients [13,19], and the remaining studies included only adult patients [6,8,9,[14][15][16][17][18][20][21][22][23][24][25][26][27][28][29][30][31]. Regarding the antiepileptic drugs, most of the patients were treated with monotherapy and the commonly used drugs were phenobarbitone, phenytoin, carbamazepine, and valproic acid [6-8, 17, 20, 26].…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…Data published in the past few years have identified several risk factors related to the prognosis of adult epilepsy. Factors, such as the number of seizures before treatment, complex partial seizures, the etiology of abnormal brain structure, longer initial treatment time, depression, and abnormal brain imaging were related to the adverse treatment outcomes of epilepsy (3)(4)(5)(6)(7), but most of the studies were conducted in the whole or adult population. So far, few studies have explored the influencing factors of ASM on the treatment outcomes of elderly patients with new-onset epilepsy, especially in the Chinese population.…”
Section: Introductionmentioning
confidence: 99%